2004
DOI: 10.4049/jimmunol.173.1.251
|View full text |Cite
|
Sign up to set email alerts
|

LIGHT Expression by Mucosal T Cells May Regulate IFN-γ Expression in the Intestine

Abstract: The TNF superfamily of cytokines play an important role in T cell activation and inflammation. Sustained expression of lymphotoxin-like inducible protein that competes with glycoprotein D for binding herpesvirus entry mediator on T cells (LIGHT) (TNFSF14) causes a pathological intestinal inflammation when constitutively expressed by mouse T cells. In this study, we characterized LIGHT expression on activated human T cell subsets in vitro and demonstrated a direct proinflammatory effect on regulation of IFN-γ. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 52 publications
(73 reference statements)
8
58
0
Order By: Relevance
“…1A), contrary to cells isolated from enzymatically disrupted tissue, which do not stain for surface LIGHT protein. Cells from the inflamed or uninvolved colon (shown), small bowel, or rectum consistently expressed membrane LIGHT, although expression was not detected in cells from the PB or draining mesenteric lymph nodes whether inflamed or not (11). LIGHT expression diminished over 24 -48 h in culture, but could be rapidly induced to maximal levels by PMA and ionomycin (P/I) activation, in accordance with the induction profile characteristic of LP T cells (Fig.…”
Section: Light Is Constitutively Expressed On Mucosal T and Nk Cellsmentioning
confidence: 64%
See 3 more Smart Citations
“…1A), contrary to cells isolated from enzymatically disrupted tissue, which do not stain for surface LIGHT protein. Cells from the inflamed or uninvolved colon (shown), small bowel, or rectum consistently expressed membrane LIGHT, although expression was not detected in cells from the PB or draining mesenteric lymph nodes whether inflamed or not (11). LIGHT expression diminished over 24 -48 h in culture, but could be rapidly induced to maximal levels by PMA and ionomycin (P/I) activation, in accordance with the induction profile characteristic of LP T cells (Fig.…”
Section: Light Is Constitutively Expressed On Mucosal T and Nk Cellsmentioning
confidence: 64%
“…LIGHT expression diminished over 24 -48 h in culture, but could be rapidly induced to maximal levels by PMA and ionomycin (P/I) activation, in accordance with the induction profile characteristic of LP T cells (Fig. 1A) (11).…”
Section: Light Is Constitutively Expressed On Mucosal T and Nk Cellsmentioning
confidence: 74%
See 2 more Smart Citations
“…19 LIGHT expression has also been reported to provide costimulatory signals resulting in proliferation and cytokine production and the induction of IFN-c production in peripheral blood as well as lamina propria T cells. 20 Several studies have suggested a role of monocytes and dendritic cells in the onset and severity of IBD. For example, the depletion of monocytes and dendritic cells in DSS-induced experimental colitis resulted in the amelioration of disease symptoms.…”
Section: Discussionmentioning
confidence: 99%